Direct sequence ultra wideband system design for wireless sensor network - Azim, Md. Anwarul; Mohammad, Hafizal; Rahman, Mijanur; Amin, Nowshad (2008)
In this study, we present the suitability of UWB for WSN by simulating a DS-UWB digital transmission system using matlab. DS-UWB is a single-band approach that uses narrow UWB pulses and time-domain signal processing combined with direct sequence spread spectrum (DSSS) techniques to transmit and receive information. Due to signal spreading, transmitted power becomes very low which paves to low probability of detection and co-existence with other systems. Simple lower order modulation scheme is considered such as binary PSK PAM due to low data rate requirements of WSN. Bit error rate (BER) performance has been evaluated for both modulation technique and simulation results show that the pulse repetition coder has significant impact on performance as well as control on data rates and reliable reception. Data is successfully recovered by energy detection method (Detect and Avoid) which facilitates design simplicity at the receiver by avoiding pulse synchronization and coherent detection.